Energy Effectiveness Assessment of Composting Technologies (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The incorrect biomass composting improperly results in considerable emission of greenhouse gases, loss of effluent and composting heat into environment. The composting heat and gases utilisation is especially suitable for plant enrichment and heating of greenhouses. The mathematical model is worked out for assessment of energy effectiveness and sustainability of biomass composting process. Coefficient of energy effectiveness for traditional litter manure composting technologies is 0.45 and can be increased up to 1.50 if the effluent, composting heat, carbon dioxide and ammonia were utilised during the composting cycle.